Association between sources of stress and depressive mood in Korean adults. (June 2021) - Hwang, In Cheol; Ahn, Hong Yup
Objective: The present study investigated the association between different sources of stress and depressive mood in Korean adults. Methods: A total of 4464 adults who completed the 2018 Korean National Health and Nutrition Examination Survey were included in the analysis. Data included sources of stress, depressive mood assessed by the nine-item Patient Health Questionnaire, sociodemographic characteristics, and health-related habits. Multiple logistic regression models were applied to calculate the odds ratio for depressive mood according to each source of stress and stratified by sex and age. Results: Fully adjusted models revealed that individuals who reported a financial problem or health concern as their main source of stress were more likely to experience depressive mood; when data were stratified by sex, these associations remained significant among females only. An age-stratified analysis indicated that financial problems were associated with depressive mood in middle-aged individuals and health concerns were associated with depressive mood in elderly. Conclusion: Korean adults with specific sources of stress should be monitored for the development of emotional distress.